2017
DOI: 10.5089/9781484329610.001
|View full text |Cite
|
Sign up to set email alerts
|

Credit Growth and Economic Recovery in Europe After the Global Financial Crisis

Abstract: IMF Working Papers describe research in progress by the author(s) and are published to elicit comments and to encourage debate. The views expressed in IMF Working Papers are those of the author(s) and do not necessarily represent the views of the IMF, its Executive Board, or IMF management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…This double dip in agriculture investment is also observed at the level of aggregate EU output, and it has raised concerns over the ability of the EU economy to recover (Antoshin et al, 2017). In fact, Antoshin et al (2017) argues that the recovery has been weaker in Europe due to the double-dip recession. The authors suggest that credit constraints could be held, also, responsible for the sluggish EU recovery.…”
Section: Data On Agriculture Investment In Eu-14mentioning
confidence: 99%
See 1 more Smart Citation
“…This double dip in agriculture investment is also observed at the level of aggregate EU output, and it has raised concerns over the ability of the EU economy to recover (Antoshin et al, 2017). In fact, Antoshin et al (2017) argues that the recovery has been weaker in Europe due to the double-dip recession. The authors suggest that credit constraints could be held, also, responsible for the sluggish EU recovery.…”
Section: Data On Agriculture Investment In Eu-14mentioning
confidence: 99%
“…This study comes in a timely manner as ten years after the financial crisis the economic recovery in EU is still rather anaemic. Antoshin et al (2017) report that the EU recovery is sluggish at best, mainly due to the observed double dip recession in many of the EU Member States in the last decade. The authors argue that bank lending and credit constraints are responsible for the observed slow EU recovery.…”
mentioning
confidence: 99%
“…, capturing the impact of bank credit on the real economy. There are not many estimates for it available in the literature Antoshin et al (2017). find for 39 European countries a 10…”
mentioning
confidence: 99%
“…In the cross-country paper, this analysis is performed by John Ralyea (EUR). For details on the data and methodology, seeAntoshin et al (2017).©International Monetary Fund. Not for Redistribution…”
mentioning
confidence: 99%
“…found that about 25 percent of all recoveries are creditless, but that this share increased to 45 percent after the GFC.Bodnár et al (2014) found that between a quarter and a fifth of recoveries were creditless and real growth was permanently lower in these cases.14 Unfortunately, the credit impulse could not be calculated on transaction data due to data limitations.15 In the cross-country paper, this analysis is performed by Etienne Yehoue. For details on the data and methodology, seeAntoshin et al (2017).…”
mentioning
confidence: 99%